On trend and on the wave: carving cultural identity through active surf dress. Issue 2 (2nd April 2016) - Anderson, Jon
ABSTRACT: Clothing, as both functional and fashionable, has become a key marker in signifying and shaping personal identity. This is particularly clear in a range of "lifestyle sports" [Wheaton, B. 2004. "Introduction: Mapping the Lifestyle Sportscape." In Understanding Lifestyle Sports: Consumption, Identity, and Difference, edited by B. Wheaton, 1–28. London: Routledge], including the array of practices associated with the culture of surfing. This paper examines the ways in which companies market performance clothing to surfers. By critically analysing the ways in which wetsuits, rash vests, body gloves, and neoprene boots are advertised by companies such as Billabong, Quiksilver, RipCurl, and O'Neill, this paper outlines how particular engagements with waves are designed into these forms of dress, and how specific cultural performances and identities are encouraged through their marketing. The paper suggests that four cultural ideals become integral to the "dress code" for performance surf wear, namely: (1) Unique Surfing Performance, (2) Cultural Authenticity, (3) Transient Engagements, and (4) Cyborgian Skin. The paper will argue how this marketing of active surf dress is important as it not only signifies particular types of identity within surfing culture, but also valorizes specific types of communion with the surf zone.